PM2.5 Concentration Pattern in ASEAN Countries Based on Population Density: Pola Konsentrasi PM2.5 di Negara-negara ASEAN Berdasarkan Kepadatan Penduduk - Teguh Panuju, Achmad Yahya; Usman, Mustofa (Procedia of Engineering and Life Science, 2023)
The concentration of PM2.5 in ambient air is one of the indicators of air quality that affects public health. This pollutant is considered hazardous due to its small size, which allows it to enter the lungs and remain suspended in the air for a considerable amount of time. Identifying the patterns of PM2.5 concentration distribution is important to recognize the influential factors in increasing PM2.5 concentrations, thus enabling better formulation of solutions. This study analyzed the patterns of PM2.5 concentrations in three ASEAN countries: Indonesia, Vietnam, and Thailand. Four randomly selected measurement locations were chosen in each country, with two locations in densely populated areas and two others in low-density areas. The sample data of PM2.5 concentrations were analyzed using nested factor analysis of variance, which allowed the relationship between the taken parameters, namely country, location, and population density classification, to be determined. The results revealed that all parameters had a significant influence on PM2.5 concentrations.